Analysis of Secondary Education with regard to the School Education Sector Plan (SESP) 2022/23-2031/32 of Nepal - Pradhananga, Nisha (Khwopa Journal, 2024)
Secondary education plays a critical role in shaping the future of individuals and societies by bridging the gap between basic education and higher education or the workforce. Over the years, global secondary education policies have evolved to address issues such as accessibility, equity, quality, and relevance to the demands of the 21st century. This study analyzes secondary education policy of Nepal with regard to School Education Sector Plan (SESP) 2022/23-2031/32 with their objectives and strategiesThe findings reveal that the SESP signifies a shift in policy towards holistic student development, focusing on quality improvement, equity promotion, and relevance to the modern job market. The policy emphasizes integrating vocational and technical education, enhancing teacher training, and fostering partnerships with industry stakeholders. However, the study identifies challenges in implementing the SESP, including resource constraints, infrastructure gaps, and regional disparities in execution.The conclusion highlights that while the SESP offers a progressive roadmap for transforming secondary education, its success will depend on overcoming these barriers. Addressing implementation challenges and ensuring continuous stakeholder engagement will be crucial to achieving the policy's ambitious goals and improving education system of Nepal.